A transient heat and mass transfer CFD simulation for proton exchange membrane fuel cells (PEMFC) with a dead-ended anode channel. (June 2020) - Peng, Yeping; Mahyari, Hamed Moradi; Moshfegh, Abouzar; Javadzadegan, Ashkan; Toghraie, Davood; Shams, Mehrzad; Rostami, Sara
Abstract: In the present study, a three-dimensional, and transient heat and mass transfer model is developed for proton exchange membrane fuel cells (PEMFC) with a dead-ended anode channel. In order to obtain the temporal volume fraction of water saturation in fuel cell channels and gas diffusion layers (GDL), transport equations for continuity, momentum, species, energy, and electric charge are all solved in a coupled manner alongside a model for water saturation through a gas-liquid two-phase flow approach. Moreover, concerning the anode channel, the fuel cell performance is examined in the absence and presence of a purge mechanism, and is characterized via functional parameters such as deliverable electrical current density, concentration of hydrogen and nitrogen as well as saturated water within the anode and GDL. Effects of various inlet gas pressures (2×10 4, 5×10 4 and 7×10 4  Pa) and relative humidity (0, 50, 100%) are studied. After a thorough validation with the experimental results, the simulations show that accumulation of water and increase of nitrogen concentration in anode channel are mechanistically linked with hydrogen depletion and cell performance drop in form of decline in electrical current density. Periodic purging of accumulated constituents show cyclic improvement in the following parameters: fuel cell performance, hydrogen utilization, and water management. When the discharge valve opens at t  = 960 s, and after purging right before the channel end is blocked at t  = 990 s. Even 30 s after opening the channel end, there is still an amount of water in the layer of anode gas diffusion layer.